2022
DOI: 10.1038/s41598-022-20348-8
|View full text |Cite|
|
Sign up to set email alerts
|

Post-stroke respiratory complications using machine learning with voice features from mobile devices

Abstract: Abnormal voice may identify those at risk of post-stroke aspiration. This study was aimed to determine whether machine learning algorithms with voice recorded via a mobile device can accurately classify those with dysphagia at risk of tube feeding and post-stroke aspiration pneumonia and be used as digital biomarkers. Voice samples from patients referred for swallowing disturbance in a university-affiliated hospital were collected prospectively using a mobile device. Subjects that required tube feeding were fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…[38] Some studies have employed the Praat program to extract these sound parameters and analyze each indicator, either using voice-only or combining voice with clinical data indicators, trained with algorithms such as Logistic Regression, Decision Tree, Random Forest, SVM, GMM, and XGBoost. [12] Another study reported the results of dysphagia prediction using speci c phonation or articulation features trained using support vector machine (SVM), random forest, and other methods. [39] However, these studies have limitations in that they only analyzed speci c numerical indicators of voice and failed to analyze the overall voice itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[38] Some studies have employed the Praat program to extract these sound parameters and analyze each indicator, either using voice-only or combining voice with clinical data indicators, trained with algorithms such as Logistic Regression, Decision Tree, Random Forest, SVM, GMM, and XGBoost. [12] Another study reported the results of dysphagia prediction using speci c phonation or articulation features trained using support vector machine (SVM), random forest, and other methods. [39] However, these studies have limitations in that they only analyzed speci c numerical indicators of voice and failed to analyze the overall voice itself.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Previous studies analyzing the voice of patients with dysphagia have reported signi cant changes in parameters such as RAP, SHIM, and NHR due to aspiration into the airway. [11][12][13][14] However, these studies often extracted speci c vocal parameters rather than analyzing the patient's voice itself, which may limit their universal application in diagnosis and monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Engineering and Computing (Sarraf Shirazi et al, 2012;Sarraf Shirazi et al, 2014), IEEE Transaction of Biomedical Engineering (Sejdic et al, 2013), IEEE Journal of Biomedical and Health Informatics (Shu et al, 2022), and Scientific Reports (Park et al, 2022) that spanned across the clinical, engineering, and interdisciplinary science fields.…”
Section: Applicability Concernsmentioning
confidence: 99%
“…The authors attempted to separate the sounds of breathing and swallowing through an aural and visual examination of the time-frequency signal spectrum. On the other hand, while Frakking et al (2022) made use of an omnidirectional condenser microphone (C417, AKG Acoustics, Vienna, Austria) in the form of a circular O-ring lateral to the cricoid cartilage, Park et al (2022) recorded the speaking sound using an iPad (with an embedded microphone) placed 20 cm in front of the participants' faces (Umayahara et al, 2018). The sampling frequency was 44.1 kHz and was band-passed between Regarding the protocol for measurement, most of them referred to the standard swallowing assessment procedures that fed food/ liquid with different consistencies or thicknesses (Lee et al, 2006;Lee et al, 2011;Merey et al, 2012;Frakking et al, 2022;Shu et al, 2022).…”
Section: Instruments and Testing Proceduresmentioning
confidence: 99%
See 1 more Smart Citation